Treatment Efficacy of Sofosbuvir and Ribavirin Combination at Two Weeks in Chronic Hepatitis C - Aqsa Naseer, Saima Ambreen, Muhammad Faheem, Sadia Ahmed, Madiha, Habib Ur Rehman, Humaira Naseem, Faiza Aslam, Hamamatul Bushra, Muhammad Umar, Aqsa Naseer, Saima Ambreen, Muhammad Faheem, Sadia Ahmed, Madiha, Habib Ur Rehman, Humaira Naseem, Faiza Aslam, Hamamatul Bushra, Muhammad Umar (Journal of Rawalpindi Medical College, 2017)
Background:To determine the effectiveness of sofosbuvir plus ribavirin in terms of frequency of negative qualitative PCR at 2nd week of treatment in chronic hepatitis C patients with genotype 3. Methods: In this case control study 60 patients with hepatitis C who were planned to receive sofobuvir and ribavarin combination therapy were included . Patients included were chronically infected with hepatitis C virus genotype 3 for whom treatment with peg-interferon is not an option and have contraindication for their use like decompensated liver disease, and patients are either non responder or relapsers to previous interferon based therapy. Pregnant or breast-feeding women, patients taking any of the medications which had interactions with sofosbuvir and patients who had not been compliant to sofosbuvir plus ribavirin therapy were excluded. Sofosbuvir was given in dose 400 mg once daily and ribavirin was given in dose of 400 or 600 twice daily(if weight <75kg or >75kg respectively). Patients were followed at 2nd week of treatment and qualitative PCR for HCV RNA was carried out Results:Total sixty patients fulfilling the inclusion criteria were included in this study. Overall efficacy of sofosbuvir and ribavirin combination was 91. 7%. Majority of patients 55(91.7%) attained negative PCR for HCV RNA at2nd week of treatment). Conclusion: Sofosbuvir plus ribavirin is an effective Treatment regimen as far as viral clearance at 2nd week of treatment is considered.